Genome-Wide Association Mapping Reveals Novel Putative Gene Candidates Governing Reproductive Stage Heat Stress Tolerance in Rice - Ravikiran, K. T.; Gopala Krishnan, S.; Abhijith, K. P.; Bollinedi, H.; Nagarajan, M.; Vinod, K. K.; Bhowmick, P. K.; Pal, Madan; Ellur, R. K.; Singh, A. K. (Frontiers in Genetics, 2022)
Temperature rise predicted for the future will severely affect rice productivity because the crop is highly sensitive to heat stress at reproductive stage. Breeding tolerant varieties is an economically viable option to combat heat stress, for which the knowledge on target genomic regions associated with the reproductive stage heat stress tolerance (RSHT) is essential. A set of 192 rice genotypes of diverse origin were evaluated under natural field conditions through staggered sowings for RSHT using two surrogate traits, spikelet fertility and grain yield which showed significant reduction under heat stress. Genotyped using a 50k SNP array, the association analysis identified 10 quantitative trait nucleotides (QTNs) for grain yield, of which one QTN (qHTGY8.1; per cent variation explained (PVE) of 19.9%) was consistent across the three different models used. Another QTN, (qHTGY1.1) which was identified only in one of the models, also showed a high PVE of 23.2%. A total of 22 QTNs were observed for spikelet fertility among which qHTSF7.1 (PVE: 25.1%), qHTSF4.2 (PVE: 25.9%), qHTSF1.1 (PVE: 18.9%), qHTSF1.3 (PVE: 25.7%) explained higher phenotypic variances. Of the QTNs identified, seven coincided with previous reports, while the remaining were novel. The genes near the QTNs were found associated with protein-protein interaction, protein ubiquitination, stress signal transduction etc. qualifying them to be putative for RSHT. Further investigations are necessary to validate the biological relevance of QTNs in conferring heat stress tolerance and their utilisation in the breeding programmes.